Action of a NO donor on the excitation–contraction pathway activated by noradrenaline in rat superior mesenteric artery - Ghisdal, Philippe (Blackwell Science Inc, 2000)
1. The aim of the present study was to investigate the actions of NO donors in ratsuperior mesenteric artery stimulated with noradrenaline by studying their effects on isometric tension, membrane potential (V(m)), cytosolic calcium concentration ([Ca(2+)](cyt)) and accumulation of inositol phosphates. 2. In unstimulated arteries, SNAP (S-nitroso-N-acetylpenicillamine, 10 μm) hyperpolarised V(m) by 3.0 ± 0.5 mV (n = 9). In KCl-stimulated arteries, SNAP relaxed contraction without changing V(m) and [Ca(2+)](cyt). 3. In noradrenaline-stimulated arteries, SNAP relaxed tension, repolarised V(m) and decreased [Ca(2+)](cyt) with the same potency. Responses to SNAP were unaffected by the following K(+) channel blockers: glibenclamide, 4-aminopyridine, apamin and charybdotoxin, and by increasing the KCl concentration to 25 mM. 4. In SNAP-pretreated arteries, the production of inositol phosphates and the contraction stimulated by noradrenaline were inhibited similarly. 5. The guanylate cyclase inhibitor ODQ abolished the increase in cyclic GMP content evoked by SNAP and inhibited the effects of SNAP on contraction, V(m) and accumulation of inositol phosphates in noradrenaline-stimulated artery. 6. These results indicate that, in rat superior mesenteric arteries activated by noradrenaline, inhibition of production of inositol phosphates is responsible for the effects of the NO donor SNAP on membrane potential, [Ca(2+)](cyt) and contraction through a cyclic GMP-dependent mechanism.